PENELITIAN ETNOGRAFI DALAM BIMBINGAN DAN KONSELING - Ibrahim, Nurmalahayati; Nursalim, Mochamad; All Habsyi, Bakhrudin (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study aims to examine ethnographic methods as a relevant and in-depth qualitative approach to understanding phenomena in education and counseling. Using a literature review method, the research analyzes various scholarly sources discussing the definition, characteristics, historical development, philosophical foundations, and benefits of ethnographic research, including its application in educational contexts. The findings indicate that ethnography emphasizes the researcher’s direct engagement in the cultural context of participants to capture deep social meaning. This approach is grounded in the philosophical perspectives of empiricism, social constructivism, and humanism, which view social reality as a co-constructed phenomenon and emphasize the importance of participants’ subjective understanding. In the field of education and counseling, ethnography has proven effective in uncovering local values and cultural practices that shape interaction dynamics in school environments. Practical examples include studies on school culture in character education and the exploration of counseling values within local traditions such as Bau Nyale in Lombok. Moreover, recent developments highlight the rise of virtual ethnography and netnography as responses to the digital transformation of society. In conclusion, ethnographic research not only provides a holistic understanding of culture but also offers practical contributions to the design of educational and counseling interventions that are contextual, inclusive, and rooted in local wisdom.